Hard carbon negative electrode material and preparation method thereof
By doping nitrogen and oxygen elements and optimizing the preparation process, the lack of performance of hard carbon negative electrode materials in sodium ion batteries is solved, the high-rate performance and conductivity are improved, and the industrial application of materials is promoted.
Patent Information
- Application Number
- CN202411632221.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-14
AI Technical Summary
The existing hard carbon anode materials have low electrode potential, poor rate performance and cycle stability in sodium ion batteries, which hinder their industrial application.
By doping nitrogen and oxygen elements, a hard carbon negative electrode material was prepared, with a nitrogen content of 2 to 5 wt%, and an oxygen content of 0.1 to 1 wt%, and a specific preparation process was used to improve the conductivity and electrochemical properties of the material.
It significantly improves the rate performance and conductivity of hard carbon negative electrode materials, ensures good specific capacity and first-term effect of the product, and is suitable for the high-performance needs of sodium ion batteries.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and discloses a hard carbon negative electrode material with high rate performance and a preparation method thereof. Background Art
[0002] Sodium-ion batteries have the advantages of high safety, abundant reserves and low cost, and are compatible with existing mature lithium-ion battery technology. They are expected to become a complement or substitute for lithium batteries in some areas. For sodium batteries, the development of high-performance electrode materials is the key to achieving commercial applications. Among them, hard carbon is the key and most mature negative electrode material for sodium batteries. Reasonable structural design is crucial to promoting the performance improvement of sodium-ion batteries and their industrial application.
[0003] As an amorphous carbon material, hard carbon has a naturally poor electrical conductivity due to its disordered graphite crystallites and amorphous region composition. It is difficult to construct a superposition theoretical model. The hard carbon negative electrode under existing technology still has the disadvantages of low electrode potential, poor rate performance and cycle stability. These factors seriously hinder the industrial application of hard carbon negative electrode materials. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention proposes a hard carbon negative electrode material and a preparation method, which can improve the rate performance and conductivity while ensuring that the product has good specific capacity and initial efficiency.
[0005] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:
[0006] On the one hand, the present invention provides a hard carbon negative electrode material, wherein nitrogen and oxygen elements are doped, wherein the nitrogen content is 2-5wt%, and the oxygen content is 0.1-1wt%; and the hard carbon negative electrode material is required to have the following characteristics:
[0007] i) The conductivity σ at a pressure of 5Mpa satisfies 12S / cm≤σ≤16S / cm;
[0008] ii) When discharged at a rate of 0.1C, the discharge capacity from the open circuit voltage to 0.1V is ≥100mAh / g, accounting for ≥30% of the total discharge capacity.
[0009] Specifically, the nitrogen content includes but is not limited to 2wt%, 2.2wt%, 2.5wt%, 2.8wt%, 3wt%, 3.2wt%, 3.5wt%, 3.8wt%, 4wt%, 4.2wt%, 4.5wt%, 4.8wt%, 5wt% or a range between any two of them, and the oxygen content includes but is not limited to 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt% or a range between any two of them;
[0010] Specifically, the conductivity σ of the hard carbon negative electrode material under a pressure of 5 MPa satisfies 12S / cm≤σ≤16S / cm, and the conductivity σ includes but is not limited to 12S / cm, 12.5S / cm, 13S / cm, 13.5S / cm, 14S / cm, 14.5S / cm, 15S / cm, 15.5S / cm, 16S / cm or a range between any two thereof;
[0011] Specifically, when the hard carbon negative electrode material is discharged at a rate of 0.1C, the discharge capacity from the open circuit voltage to 0.1V is ≥100mAh / g, including but not limited to 100mAh / g, 105mAh / g, 110mAh / g, 115mAh / g, 120mAh / g, 130mAh / g, 140mAh / g, 150mAh / g and above; the ratio of the total discharge capacity is ≥30%, including but not limited to 30%, 32%, 34%, 36%, 38%, 40%, 42%, 45% and above.
[0012] According to the hard carbon negative electrode material provided by the present invention, nitrogen is doped into carbon nanomaterials, which can change the atomic and electronic structure of the matrix, increase its conductivity, form a delocalized conjugated system of sp2 hybridized C, and significantly improve the electrochemical performance. At the same time, oxygen is also doped into the carbon nanomaterial, and by forming oxygen-containing functional groups on the surface of the hard carbon material, the specific capacity and rate performance of the hard carbon negative electrode material can be significantly improved.
[0013] According to the hard carbon negative electrode material provided by the present invention, the electrical conductivity σ of the hard carbon negative electrode material under a pressure of 5Mpa satisfies 12S / cm≤σ≤16S / cm; at the same time, when discharged at a rate of 0.1C, the discharge capacity from the open circuit voltage to 0.1V is ≥100mAh / g, and the ratio of the open circuit voltage to the total discharge capacity is ≥30%, indicating that the hard carbon negative electrode material of the present invention has excellent performance under high rate discharge.
[0014] On the other hand, the present invention also provides a method for preparing the hard carbon negative electrode material, comprising the following steps:
[0015] 1) mixing a hard carbon precursor with a carbohydrate, placing the mixture in a ball mill for dry milling and coating to obtain a pre-carbonized precursor;
[0016] 2) The pre-carbonized precursor is subjected to a pre-carbonization reaction in a mixed atmosphere of nitrogen and hydrogen, and then a nitrogen source is introduced to perform a nitrogen doping reaction to obtain a nitrogen-doped material;
[0017] 3) The nitrogen-doped material is subjected to a high-temperature carbonization reaction, and then an oxygen-containing gas is introduced to carry out an oxidation reaction to obtain a hard carbon negative electrode material.
[0018] In one embodiment, the hard carbon precursor described in step 1) is selected from one or more of high molecular polymers, biomass, and coke, preferably one or more of phenolic resin, epoxy resin, polyfurfuryl alcohol, bituminous coal, anthracite, sub-bituminous coal, coconut shell, walnut shell, bamboo, straw, cellulose, lignin, needle coke, asphalt coke, petroleum coke, and asphalt, more preferably one or more of phenolic resin and anthracite.
[0019] In one embodiment, the carbohydrate in step 1) is a compound composed of three elements: carbon, hydrogen and oxygen, and is specifically used as an additive. The carbohydrate is selected from one or more of starch, sucrose, glucose, polyoxymethylene, maltose, dextrin, and polyether ketone, preferably one or more of starch and glucose.
[0020] In one embodiment, the mass ratio of the hard carbon precursor to the carbohydrate in step 1) is 1:0.1-1, including but not limited to 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1 or a range composed of any two thereof, preferably 1:0.3-0.8.
[0021] In one embodiment, the dry ball milling in step 1) uses a ball mill, and the motor speed of the ball mill is 500-1800rpm, preferably 800-1500rpm; the ball milling time is 0.5-20h, preferably 5-15h; specifically, the motor speed of the ball mill includes but is not limited to 500rpm, 700rpm, 900rpm, 1000rpm, 1200rpm, 1400rpm, 1600rpm, 1800rpm or a range between any two thereof, and the ball milling time includes but is not limited to 0.5h, 1h, 3h, 5h, 8h, 10h, 12h, 14h, 16h, 18h, 20h or a range between any two thereof;
[0022] Preferably, the ball mill comprises a grinding ball 1 and a grinding ball 2, the diameter of the grinding ball 1 is in the range of 2 to 6 mm, and the diameter ratio of the grinding ball 1 to the grinding ball 2 is in the range of 1 to 6:1, more preferably 2 to 4:1; specifically, the diameter of the grinding ball 1 includes but is not limited to 2 mm, 3 mm, 4 mm, 5 mm, 6 mm or a range between any two thereof, and the diameter ratio of the grinding ball 1 to the grinding ball 2 includes but is not limited to 1:1, 2:1, 3:1, 4:1, 5:1, 6:1 or a range between any two thereof;
[0023] Preferably, the total weight ratio of the grinding balls 1 and 2 to the total weight of the hard carbon precursor and the carbohydrate is 1 to 18:1, including but not limited to 1:1, 3:1, 5:1, 7:1, 9:1, 10:1, 12:1, 14:1, 16:1, 18:1 or a range between any two of them, more preferably 3 to 6:1.
[0024] In one embodiment, the pre-carbonization reaction in step 2) is carried out at a temperature of 200-900°C, preferably 500-700°C, and for a time of 0.5-10h, preferably 2-4h; specifically, the temperature includes but is not limited to 200°C, 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, 900°C or a range between any two of them, and the time includes but is not limited to 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h or a range between any two of them.
[0025] In one embodiment, the mixed atmosphere of nitrogen and hydrogen in step 2) has a gas flow rate of 100 to 1000 mL / min, including but not limited to 100 mL / min, 200 mL / min, 400 mL / min, 600 mL / min, 800 mL / min, 1000 mL / min or a range between any two thereof, preferably 200 to 600 mL / min;
[0026] Preferably, the volume percentage of hydrogen in the mixed atmosphere is 0.1-10 vol%, including but not limited to 0.1 vol%, 0.5 vol%, 1 vol%, 2 vol%, 4 vol%, 6 vol%, 8 vol%, 10 vol% or any range therebetween, more preferably 1-5 vol%.
[0027] In one embodiment, the nitrogen doping reaction in step 2) has a temperature of 150-650°C, preferably 250-550°C; and a time of 0.5-10 h, preferably 1-4 h; specifically, the temperature includes but is not limited to 150°C, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C or a range between any two of them, and the time includes but is not limited to 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h or a range between any two of them.
[0028] In one embodiment, the nitrogen source in step 2) is selected from lower amines, i.e., gaseous or volatile liquid amines, preferably gaseous organic amine compounds, more preferably one or more of methylamine, ethylamine, dimethylamine, and trimethylamine, further preferably one or more of methylamine and dimethylamine;
[0029] Preferably, the nitrogen source has a flow rate of 10 to 500 mL / min in gaseous state, including but not limited to 10 mL / min, 50 mL / min, 100 mL / min, 200 mL / min, 300 mL / min, 400 mL / min, 500 mL / min or a range between any two thereof, more preferably 200 to 300 mL / min.
[0030] According to the preparation method provided by the present invention, in the aforementioned step 2) pre-carbonization process, nitrogen-hydrogen mixed gas reduction is used to fully remove oxygen from the hard carbon precursor and the additive, reduce the generation of nitrogen oxides NOx in the subsequent nitrogen doping process, and retain the carbonization yield to the greatest extent; the additive is easily decomposed into carbon dioxide and water under high temperature conditions, overflowing from the material to realize a pore structure, providing more penetration space for subsequent nitrogen doping and oxygen doping.
[0031] At the same time, in the aforementioned step 2), low-level amines are also used as nitrogen sources for nitrogen doping. During the process, no H2 will be decomposed to reduce the generation of hidden dangers. In addition, pyridine carbon CNC and graphite carbon N-C3 structures are more easily generated during the process, and the generation of NC structures can be reduced, thereby effectively enhancing the nitrogen doping effect and achieving an improvement in electronic conductivity. In addition, the use of low-level amines as nitrogen sources can reduce the generation of NO structures in subsequent oxidative doping, thereby avoiding the unstable generation of NOx by the structure at high temperatures.
[0032] In one embodiment, the high temperature carbonization reaction in step 3) is carried out at a temperature of 1000-1600°C, preferably 1200-1500°C; and for a time of 1-5h, preferably 2-3h; specifically, the temperature includes but is not limited to 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C, 1600°C, or a range between any two thereof, and the time includes but is not limited to 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, or a range between any two thereof;
[0033] In some specific examples, the high temperature carbonization reaction is carried out in a protective gas environment; preferably, the protective gas is selected from one of the inert gases, such as nitrogen, helium, and argon;
[0034] Preferably, the protective gas flow rate is 100-500 mL / min, including but not limited to 100 mL / min, 200 mL / min, 300 mL / min, 400 mL / min, 500 mL / min or a range between any two thereof, preferably 200-300 ml / min.
[0035] In one embodiment, the oxidation reaction in step 3) is carried out at a temperature of 150 to 550°C, preferably 250 to 450°C, and for a time of 0.5 to 2.5 h, preferably 1 to 2 h; specifically, the temperature includes but is not limited to 150°C, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C or a range between any two of them, and the time includes but is not limited to 0.5 h, 0.8 h, 1 h, 1.3 h, 1.5 h, 1.8 h, 2 h, 2.2 h, 2.5 h or a range between any two of them.
[0036] In one embodiment, the oxygen-containing gas in step 3) has a flow rate of 50 to 300 mL / min, including but not limited to 50 mL / min, 100 mL / min, 150 mL / min, 200 mL / min, 250 mL / min, 300 mL / min or a range between any two thereof, preferably 100 to 200 mL / min;
[0037] Preferably, the oxygen-containing gas may be 100% pure oxygen, or an oxygen-containing mixed gas, preferably an oxygen-nitrogen mixed gas;
[0038] Specifically, in the oxygen-nitrogen mixed gas, the volume percentage of oxygen is 0.1-10 vol%, including but not limited to 0.1 vol%, 0.5 vol%, 1 vol%, 2 vol%, 4 vol%, 6 vol%, 8 vol%, 10 vol% or a range between any two thereof, preferably 0.5-3 vol%.
[0039] After the pre-carbonization reaction in step 2) of the present invention is completed, the temperature is cooled and then a nitrogen source is introduced to carry out a nitrogen doping reaction, wherein the cooling is preferably directly cooled to the nitrogen doping reaction temperature; similarly, after the high-temperature carbonization reaction in step 3) of the present invention is completed, the temperature is cooled and then an oxygen-containing gas is introduced to carry out an oxidation reaction, wherein the cooling is preferably directly cooled to the oxidation reaction temperature.
[0040] In one embodiment, steps 2) and 3) are performed in a rotary kiln, and the rotation speed of the rotary kiln is 1 to 10 r / min, including but not limited to 1 r / min, 2 r / min, 3 r / min, 4 r / min, 5 r / min, 6 r / min, 7 r / min, 8 r / min, 9 r / min, 10 r / min or a range between any two thereof, preferably 6 to 10 r / min.
[0041] According to the preparation method provided by the present invention, in the aforementioned step 3) carbonization process, volatile matter, surface functional groups and impurity elements are effectively removed by high-temperature sintering, and the carbon skeleton is rearranged, open pores are closed, and surface defects are repaired. Finally, oxygen-containing functional groups are generated on the carbon surface by oxygen-containing doping under low temperature conditions, which can effectively improve the sodium absorption efficiency and rate performance.
[0042] Compared with the prior art, the beneficial effects of the technical solution of the present invention are:
[0043] (1) The present invention uses low-level amines for nitrogen doping, which not only improves the doping effect and enhances the electronic conductivity of the material; it is also safe and environmentally friendly and suitable for large-scale production;
[0044] (2) The present invention introduces carbohydrates as additives to form pores through gas overflow, which effectively improves the subsequent nitrogen and oxygen doping effect, achieves simultaneous enhancement of electronic conductivity and sodium absorption rate, and has good rate performance.
[0045] (3) The various steps of the present invention are closely linked, and the process is precise to control the content of pyridine carbon CNC, graphite carbon N-C3 and oxygen-containing functional groups in the material. The nitrogen content of the hard carbon negative electrode material finally obtained is 2-5wt%, the oxygen content is 0.1-1wt%, and the conductivity σ under a pressure of 5Mpa satisfies 12S / cm≤σ≤16S / cm; and when discharged at a rate of 0.1C, the open circuit voltage of the hard carbon material to 0.1V discharge capacity is ≥100mAh / g, accounting for ≥30% of the total discharge capacity. DETAILED DESCRIPTION
[0046] The present invention is further described below in conjunction with the embodiments, but the present invention is not limited to the listed embodiments.
[0047] In the embodiments and comparative examples of the present invention, the sources of the main raw materials used are as follows. Unless otherwise specified, other raw materials and reagents were purchased from commercial sources:
[0048] Phenolic resin: purity ≥99.5wt%, Wanhua Chemical;
[0049] Anthracite: ash content ≤ 3wt%, Yangmei;
[0050] Coconut shell: ash ≤ 3wt%, Wenchang, Hainan;
[0051] Asphalt: ash ≤ 1wt%, Hebei Carbon Nine;
[0052] Starch: purity ≥98wt%, Minghao Chemical;
[0053] Glucose: purity ≥98wt%, Minghao Chemical;
[0054] Maltose: purity ≥98wt%, Minghao Chemical;
[0055] Polyoxymethylene: purity ≥98wt%, Shuangying Chemical;
[0056] Methylamine: purity ≥99.9wt%, Wanhua Chemical;
[0057] Ethylamine: purity ≥99.9wt%, Wanhua Chemical;
[0058] Dimethylamine: purity ≥99.9wt%, Wanhua Chemical;
[0059] Trimethylamine: purity ≥99.9wt%, Wanhua Chemical;
[0060] Nitrogen: purity ≥ 99.9wt%, Wanhua Chemical;
[0061] Helium: purity ≥ 99.9wt%, Wanhua Chemical;
[0062] Argon: purity ≥99.9wt%, Wanhua Chemical.
[0063] The main analytical methods used in the examples and comparative examples of the present invention are:
[0064] Oxygen and nitrogen content test: The oxygen and nitrogen element analyzer measures the oxygen and nitrogen content in the hard carbon negative electrode material (GB 3095-2012).
[0065] Resistivity test: After 3g of hard carbon negative electrode material sample powder is fully dried, use a tablet press to press the powder into a circular membrane with a radius of 0.8cm at a relatively low pressure, and place the membrane in a cylindrical sample tube with two electrode sheets at the top and bottom. Apply pressure gradually at both ends to ensure good contact between the sample and the electrode sheets and pass a direct current. When the pressure reaches 5MPa, maintain the pressure for 10s and record the conductivity value at this time.
[0066] Power-off test method: when discharging at a constant current of 0.1C rate, the discharge capacity of the hard carbon negative electrode material is measured and recorded as the first discharge capacity; when discharging from the open circuit voltage to 0.1V, the discharge capacity of the hard carbon negative electrode material is measured and recorded as the second discharge capacity; when continuously discharging at a constant current of 0.1C rate to 0.005V, the discharge capacity of the hard carbon negative electrode material is measured and recorded as the total discharge capacity.
[0067] Ball mill: pendulum ball mill, Hefei Kejing.
[0068] In order to better understand the hard carbon negative electrode material and preparation method of the present invention, specific implementation examples are provided below, which are not limitations of the present invention.
[0069] Example 1
[0070] S1: 10 g of phenolic resin, 3 g of starch, 97.5 g of zirconium beads with a diameter of 6 mm, and 32.5 g of zirconium beads with a diameter of 2 mm were added to a ball mill respectively, the motor speed of the ball mill was set to 800 rpm, and the ball milling time was 5 h to obtain a pre-carbonized precursor A;
[0071] S2: The precursor A obtained in S1 is pre-carbonized in a rotary tube furnace, the temperature is set to 500°C, the rotary furnace speed is 6r / min, and a nitrogen-hydrogen mixed gas mixed with 5 vol% hydrogen is continuously introduced at a flow rate of 200ml / min for purging. After the pre-carbonization time is 2h, the pre-carbonized material B is obtained;
[0072] S3: After S2 is completed, the temperature is lowered to 250° C., the nitrogen-hydrogen mixed gas is switched to methylamine gas, and methylamine gas is continuously introduced at a flow rate of 200 ml / min for 1 hour to obtain the corresponding nitrogen-doped material C;
[0073] S4: After S3 is completed, the temperature is further raised to 1200° C., the methylamine gas is switched to nitrogen gas, which is continuously introduced at a flow rate of 200 ml / min, and the obtained nitrogen-doped material C is subjected to high-temperature carbonization for 2 hours to obtain a carbonized material D;
[0074] S5: After S4 is completed, the temperature is cooled to 250° C., and a mixed gas of oxygen and nitrogen containing 0.5 vol% oxygen is introduced at a flow rate of 100 ml / min for purging. After 1 hour, a hard carbon negative electrode material is obtained.
[0075] Oxygen and nitrogen content: The nitrogen content of the prepared hard carbon negative electrode material measured by an oxygen and nitrogen element analyzer is 2wt%, and the oxygen content is 0.1wt%;
[0076] Resistivity test: conductivity σ=12S / cm under 5Mpa pressure;
[0077] Withholding test: When discharged at a rate of 0.1C, the open circuit voltage of the hard carbon material is 111 mAh / g at 0.1V, accounting for 31% of the total discharge capacity.
[0078] Example 2
[0079] S1: 10 g anthracite, 5 g glucose, 144 g zirconium beads with a diameter of 6 mm, and 36 g zirconium beads with a diameter of 1.5 mm were added to a ball mill respectively, the motor speed of the ball mill was set to 1000 rpm, and the ball milling time was 10 h to obtain a pre-carbonized precursor A;
[0080] S2: The precursor A obtained in S1 is pre-carbonized in a rotary tube furnace, the temperature is set to 700°C, the rotary furnace speed is 8r / min, and a nitrogen-hydrogen mixed gas mixed with 3 vol% hydrogen is continuously introduced at a flow rate of 350ml / min for purging. After the pre-carbonization time is 3h, the pre-carbonized material B is obtained;
[0081] S3: After S2 is completed, the temperature is lowered to 400°C, the nitrogen-hydrogen mixed gas is switched to ethylamine gas, and the gas is continuously introduced at a flow rate of 250 ml / min for 2 hours to obtain the corresponding nitrogen-doped material C;
[0082] S4: After S3 is completed, the temperature is further raised to 1300° C., the ethylamine gas is switched to nitrogen gas, which is continuously introduced at a flow rate of 300 ml / min, and the obtained nitrogen-doped material C is subjected to high-temperature carbonization for 3 hours to obtain a carbonized material D;
[0083] S5: After S4 is completed, the temperature is cooled to 350° C., and a mixed gas of oxygen and nitrogen containing 1 vol% oxygen is introduced at a flow rate of 150 ml / min for purging. After 2 hours, a hard carbon negative electrode material is obtained.
[0084] Oxygen and nitrogen content: The nitrogen content of the prepared hard carbon negative electrode material measured by an oxygen and nitrogen element analyzer is 3wt% and the oxygen content is 0.3wt%;
[0085] Resistivity test: conductivity σ=13.2S / cm under 5Mpa pressure;
[0086] Withholding test: When discharged at a rate of 0.1C, the discharge capacity of the hard carbon material from the open circuit voltage to 0.1V is 100mAh / g, accounting for 40% of the total discharge capacity.
[0087] Example 3
[0088] S1: 10 g coconut shell, 8 g maltose, 225 g zirconium beads with a diameter of 5 mm and 45 g zirconium beads with a diameter of 1 mm were added to the ball mill respectively, the motor speed of the ball mill was set to 1200 rpm, and the ball milling time was 15 h to obtain the pre-carbonized precursor A;
[0089] S2: Precursor A obtained in S1 is placed in a rotary tube furnace for pre-carbonization. The temperature is set to 600°C and the rotary furnace speed is 10r / min. A nitrogen-hydrogen mixed gas mixed with 5 vol% hydrogen is continuously introduced at a flow rate of 600ml / min for purging. After pre-carbonization for 4h, pre-carbonized material B is obtained;
[0090] S3: After S2 is completed, the temperature is lowered to 550° C., the nitrogen-hydrogen mixed gas is switched to dimethylamine gas, and the gas is continuously introduced at a flow rate of 300 ml / min for 4 hours to obtain the corresponding nitrogen-doped material C;
[0091] S4: After S3 is completed, the temperature is further raised to 1500° C., the dimethylamine gas is switched to helium, which is continuously introduced at a flow rate of 300 ml / min, and the obtained nitrogen-doped material C is subjected to high-temperature carbonization for 2 hours to obtain a carbonized material D;
[0092] S5: After S4 is completed, the temperature is cooled to 450° C., and a mixed gas of oxygen and nitrogen containing 2 vol% oxygen is introduced at a flow rate of 200 ml / min for purging. After 2 hours, a hard carbon negative electrode material is obtained.
[0093] Oxygen and nitrogen content: The nitrogen content of the prepared hard carbon negative electrode material measured by an oxygen and nitrogen element analyzer is 5wt% and the oxygen content is 0.8wt%;
[0094] Resistivity test: conductivity σ=15.5S / cm under 5Mpa pressure;
[0095] Withholding test: When discharged at a rate of 0.1C, the open circuit voltage of the hard carbon material is discharged at 0.1V with a discharge capacity of 110 mAh / g, accounting for 30% of the total discharge capacity.
[0096] Example 4
[0097] S1: 10 g of asphalt, 6 g of polyoxymethylene, 200 g of zirconium beads with a diameter of 5 mm, and 40 g of zirconium beads with a diameter of 1 mm were added to a ball mill respectively, the motor speed of the ball mill was set to 1500 rpm, and the ball milling time was 12 h to obtain a pre-carbonized precursor A;
[0098] S2: The precursor A obtained in S1 is pre-carbonized in a rotary tube furnace, the temperature is set to 600°C, the rotary furnace speed is 10r / min, and a nitrogen-hydrogen mixed gas mixed with 5vol% hydrogen is continuously introduced at a flow rate of 600ml / min for purging. After the pre-carbonization time is 4h, a pre-carbonized material B is obtained;
[0099] S3: After S2 is completed, the temperature is lowered to 550° C., the nitrogen-hydrogen mixed gas is switched to dimethylamine gas, and the gas is continuously introduced at a flow rate of 300 ml / min for 4 hours to obtain the corresponding nitrogen-doped material C;
[0100] S4: After S3 is completed, the temperature is further raised to 1500° C., the dimethylamine gas is switched to argon gas, which is continuously introduced at a flow rate of 250 ml / min, and the obtained nitrogen-doped material C is subjected to high-temperature carbonization for 3 hours to obtain a carbonized material D;
[0101] S5: After S4 is completed, the temperature is cooled to 400° C., and a mixed gas of oxygen and nitrogen containing 3 vol% oxygen is introduced at a flow rate of 250 ml / min for purging. After 3 hours, a hard carbon negative electrode material is obtained.
[0102] Oxygen and nitrogen content: The nitrogen content of the prepared hard carbon negative electrode material measured by an oxygen and nitrogen element analyzer is 5wt% and the oxygen content is 1wt%;
[0103] Resistivity test: conductivity σ=15.8S / cm under 5Mpa pressure;
[0104] Withholding test: When discharged at a rate of 0.1C, the open circuit voltage of the hard carbon material to 0.1V discharge capacity is 101 mAh / g, accounting for 38% of the total discharge capacity.
[0105] Comparative Example 1
[0106] Referring to the method of Example 1, the only difference is that starch is not added in step S1, and other operations and conditions remain unchanged to obtain a hard carbon negative electrode material.
[0107] Oxygen and nitrogen content: The nitrogen content of the prepared hard carbon negative electrode material measured by an oxygen and nitrogen element analyzer is 1wt% and the oxygen content is 0.05wt%;
[0108] Resistivity test: conductivity σ=8.5S / cm under 5Mpa pressure;
[0109] Withholding test: When discharged at a rate of 0.1C, the open circuit voltage of the hard carbon material has a discharge capacity of 82 mAh / g to 0.1V, accounting for 28% of the total discharge capacity.
[0110] Comparative Example 2
[0111] Referring to the method of Example 2, the only difference is that ethylamine is not introduced for nitrogen doping in step S3, and other operations and conditions remain unchanged to obtain a hard carbon negative electrode material.
[0112] Oxygen and nitrogen content: The nitrogen content of the prepared hard carbon negative electrode material measured by an oxygen and nitrogen element analyzer is 0.2wt%, and the oxygen content is 0.3wt%;
[0113] Resistivity test: conductivity σ=10.3S / cm under 5Mpa pressure;
[0114] Withholding test: When discharged at a rate of 0.1C, the open circuit voltage of the hard carbon material to 0.1V discharge capacity is 91 mAh / g, accounting for 38% of the total discharge capacity.
[0115] Comparative Example 3
[0116] Referring to the method of Example 3, the only difference is that low-temperature oxidation is not performed in step S5, and other operations and conditions remain unchanged to obtain a hard carbon negative electrode material.
[0117] Oxygen and nitrogen content: The nitrogen content of the prepared hard carbon negative electrode material measured by an oxygen and nitrogen element analyzer was 5.1wt% and the oxygen content was 0.04wt%;
[0118] Resistivity test: conductivity σ=11.5S / cm under 5Mpa pressure;
[0119] Withholding test: When discharged at a rate of 0.1C, the open circuit voltage of the hard carbon material has a discharge capacity of 95 mAh / g to 0.1V, accounting for 28% of the total discharge capacity.
[0120] The application of the present invention is not limited to the above embodiments. For those skilled in the art, any modification or change made within the spirit of the present invention is included in the scope of protection intended by the present invention.
Claims
1. A hard carbon negative electrode material, characterized in that: It is doped with nitrogen and oxygen elements, wherein the nitrogen content is 2-5wt%, and the oxygen content is 0.1-1wt%. At the same time, the hard carbon negative electrode material is required to have the following characteristics: i) The conductivity σ at a pressure of 5Mpa satisfies 12S / cm≤σ≤16S / cm; ii) When discharged at a rate of 0.1C, the discharge capacity from the open circuit voltage to 0.1V is ≥100mAh / g, accounting for ≥30% of the total discharge capacity.
2. A method for preparing the hard carbon negative electrode material according to claim 1, characterized in that: The following steps are involved: 1) mixing a hard carbon precursor with a carbohydrate, placing the mixture in a ball mill for dry milling and coating to obtain a pre-carbonized precursor; 2) The pre-carbonized precursor is subjected to a pre-carbonization reaction in a mixed atmosphere of nitrogen and hydrogen, and then a nitrogen source is introduced to perform a nitrogen doping reaction to obtain a nitrogen-doped material; 3) The nitrogen-doped material is subjected to a high-temperature carbonization reaction, and then an oxygen-containing gas is introduced to carry out an oxidation reaction to obtain a hard carbon negative electrode material.
3. The preparation method according to claim 2, characterized in that: The hard carbon precursor in step 1) is selected from one or more of high molecular polymers, biomass, and coke, preferably one or more of phenolic resin, epoxy resin, polyfurfuryl alcohol, bituminous coal, anthracite, sub-bituminous coal, coconut shell, walnut shell, bamboo, straw, cellulose, lignin, needle coke, asphalt coke, petroleum coke, and asphalt, more preferably one or more of phenolic resin and anthracite; and / or The carbohydrates in step 1) are selected from one or more of starch, sucrose, glucose, polyoxymethylene, maltose, dextrin, and polyetherketone, more preferably one or more of starch and glucose; and / or The mass ratio of the hard carbon precursor to the carbohydrate in step 1) is 1:0.1-1, preferably 1:0.3-0.
8.
4. The preparation method according to claim 2, characterized in that: The dry ball milling in step 1) uses a ball mill, the motor speed of the ball mill is 500-1800rpm, preferably 800-1500rpm; the ball milling time is 0.5-20h, preferably 5-15h; Preferably, the ball mill comprises a grinding ball 1 and a grinding ball 2, the diameter of the grinding ball 1 is 2 to 6 mm, and the diameter ratio of the grinding ball 1 to the grinding ball 2 is 1 to 6:1, more preferably 2 to 4:1; Preferably, the ratio of the total weight of the grinding balls 1 and 2 to the total weight of the hard carbon precursor and the carbohydrate is 1 to 18:1, more preferably 3 to 6:
1.
5. The preparation method according to claim 2, characterized in that: The pre-carbonization reaction in step 2) is carried out at a temperature of 200 to 900° C., preferably 500 to 700° C., for a time of 0.5 to 10 h, preferably 2 to 4 h; and / or The mixed atmosphere of nitrogen and hydrogen in step 2) has a gas flow rate of 100 to 1000 mL / min, preferably 200 to 600 mL / min; Preferably, the volume percentage of hydrogen in the mixed atmosphere is 0.1 to 10 vol%, more preferably 1 to 5 vol%.
6. The preparation method according to claim 2, characterized in that: The nitrogen doping reaction in step 2) is carried out at a temperature of 150 to 650° C., preferably 250 to 550° C., for a time of 0.5 to 10 h, preferably 1 to 4 h; and / or The nitrogen source in step 2) is selected from lower amines, preferably gaseous organic amine compounds, more preferably one or more of methylamine, ethylamine, dimethylamine, and trimethylamine, and further preferably one or more of methylamine and dimethylamine; Preferably, the nitrogen source has a flow rate of 10 to 500 mL / min, more preferably 200 to 300 mL / min, in gaseous state.
7. The preparation method according to claim 2, characterized in that: The high temperature carbonization reaction in step 3) is carried out at a temperature of 1000-1600° C., preferably 1200-1500° C., and for a time of 1-5 h, preferably 2-3 h.
8. The preparation method according to claim 2, characterized in that: The oxidation reaction in step 3) is carried out at a temperature of 150 to 550° C., preferably 250 to 450° C., for a time of 0.5 to 2.5 hours, preferably 1 to 2 hours; and / or The oxygen-containing gas in step 3) has a flow rate of 50 to 300 mL / min, preferably 100 to 200 mL / min; Preferably, the oxygen-containing gas may be 100% pure oxygen, or an oxygen-containing mixed gas, preferably an oxygen-nitrogen mixed gas; More preferably, the volume percentage of oxygen in the oxygen-nitrogen mixed gas is 0.1-10 vol%, preferably 0.5-3 vol%.
9. The preparation method according to claim 2, characterized in that: Steps 2) and 3) are performed in a rotary kiln, and the rotation speed of the rotary kiln is 1 to 10 r / min, preferably 6 to 10 r / min.